Hypertension of Developmental Origins: Consideration of Gut Microbiome in Animal Models - You-Lin Tain (Biomedicines, 2022)
Hypertension is the leading cause of global disease burden. Hypertension can arise from early life. Animal models are valuable for giving cogent evidence of a causal relationship between various environmental insults in early life and the hypertension of developmental origins in later life. These insults consist of maternal malnutrition, maternal medical conditions, medication use, and exposure to environmental chemicals/toxins. There is a burgeoning body of evidence on maternal insults can shift gut microbiota, resulting in adverse offspring outcomes later in life. Emerging evidence suggests that gut microbiota dysbiosis is involved in hypertension of developmental origins, while gut microbiota-targeted therapy, if applied early, is able to help prevent hypertension in later life. This review discusses the innovative use of animal models in addressing the mechanisms behind hypertension of developmental origins. We will also highlight the application of animal models to elucidate how the gut microbiota connects with other core mechanisms, and the potential of gut microbiota-targeted therapy as a novel preventive strategy to prevent hypertension of developmental origins. These animal models have certainly enhanced our understanding of hypertension of developmental origins, closing the knowledge gap between animal models and future clinical translation.